MAIN CHARACTER’S STRUGGLE AGAINSTS WOMAN OPPRESSION IN “MARLINA THE MURDERER IN FOUR ACTS” MOVIE - DESY NATALIA SIMANJUNTAK; ANNA RIANA SURYANTI TAMBUNAN; MORADA TETTY (LINGUISTICA, 2021)
This study dealt with the struggle of the main character in Marlina the Murderer in Four Acts movie. The objectives were to find out the oppressions that the main character experienced, the struggles against the oppression, and how the main character struggled against the oppression. This study used descriptive qualitative as the method to analyze the data. The researcher used Young's (1990) theory to analyze the data from the movie's script. Marlina, as the movie's main character, suffered from three kinds of oppression; marginalization, powerlessness, and violence. Marlina suffered oppression because she was powerless; she lived in poverty and patriarchal culture in Sumba. Marlina also struggles against oppression by doing feminism; they are; liberal feminism and radical feminism.